Relevance of Metabolic Activation Pathways: The Example of Clopidogrel and Prasugrel - Petersen, Karl-Uwe (Arzneimittelforschung, 2009)
Poor or lacking responses to the antiplatelet effect of clopidogrel (CAS 113665-84-2) and the attendant clinical consequences have been a growing concern for several years. This debate has been invigorated by reports suggesting the ability of inhibitors of the cytochrome P450 isoenzyme, CYP 2C19, to interfere with clopidogrel efficacy. In the present review, the mechanisms underlying clopidogrel failure are analyzed, based on an overview of the current perceptions of drug metabolismby the CYP superfamily of enzymes, and paying particular attention to the relevant properties of the newly introduced thienopyridine, prasugrel (CAS 150322-43-3). Convincing evidence indicates that the vulnerability of clopidogrel lies in its mode of activation. In a two-step sequence, both crucially dependent on the function of CYP 2C19, about 15% of a given dose of clopidogrel are converted into an active metabolite. Thus, activation is at risk or impossible in patients with the phenotype of an intermediate or poor metabolizer or, for similar reasons, in patients co-administered with a CYP 2C19 inhibitor such as the proton pump inhibitor (PPI), omeprazole. Theoretical and experimental data suggest that other PPIs such as rabeprazole do not share this ability. As opposed to clopidogrel, administered prasugrel is practically completely activated. At first sight a similar two-step process, this activation shows distinct differences: The first metabolic step is mediated by carboxylesterases and the second reaction is catalyzed by five different CYP isoenzymes, with no pivotal role for CYP 2C19 or any other CYP isoform. This setting allows the prediction that neither specific genetic traits nor pharmacokinetic drug interactions will interfere with prasugrel antiplatelet activity. Unfolding evidence, including a lack of interference by genotype and CYP 2C19 or CYP 3A4 inhibitors, has confirmed this expectation. The robust efficacy of prasugrel allows the prediction that this new thienopyridine will provide an unproblematic treatment modality, with no need for pheno- or genotyping and no special regards for co-administered drugs.
Keywords: CAS 113665-84-2; CAS 150322-43-3; Clopidogrel; Cytochrome P450; Drug interactions; Omeprazole; Polymorphism; Prasugrel; Proton pump inhibitors